Depiction of Indonesian Independence War in ’Jenderal Soedirman’ Movie (Cinematology: Journal Anthology of Film and Television Studies, 2024)
The film Jenderal Soedirman is a cinematic representation that portrays Indonesia's struggle for independence through the perspective of guerrilla warfare. However, the film also highlights the political dilemmas and differing strategies among historical figures, particularly between the paths of diplomacy and armed resistance. This study aims to analyze the narrative structure and the representation of the independence struggle in the film using Klaus Krippendorff’s content analysis approach and Roland Barthes’ semiotics. Through a qualitative method, the research examines how the film constructs meaning through signs and symbols that reinforce the notions of heroism and nationalism. The findings show that the film not only narrates General Soedirman's physical journey in guerrilla warfare but also reveals the ideological battles underlying the fight for independence. The film constructs General Soedirman as a symbol of resilience and morality in the face of colonial domination. The implications of this study affirm that cinema plays a vital role in shaping collective memory and nationalism. Furthermore, this research opens space for further exploration of historical representation in Indonesian cinema and how films can influence public understanding of the nation’s history.